PENGEMBANGAN PRODUK-PRODUK LEMBAGA KEUANGAN MIKRO SYARIAH - Sa'diyah, Mahmudatus; Arifin, Meuthiya Athifa (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
Islamic microfinance institutions is one of the pillars in the financial intermediation process. Microfinance is needed by small and medium-sized communities both for consumption and production, and also save the results of their efforts. This study aims to determine the theoretical foundations associated with the development of products Islamic microfinance institutions. The results showed that the development of products LKMS through enterprise planning process to determine the market demand, establish a strategic decision in the formation of products, improve the product, even to innovate new products as an effort to improve the quality of services and products LKMS services. Through Islamic principles in product development stage, the products can provide variation LKMS lawful and good for the benefit of society in general. Efforts related to the development of performance management products generate LKMS lead to the implementation of activities in the form of an increase in the product. It is as a form of improving managerial quality in LKMS.Keywords: Product Development and Microfinance Institutions ShariaLembaga keuangan mikro syariah merupakan salah satu pilar dalam proses intermediasi keuangan. Keuangan mikro dibutuhkan oleh kelompok masyarakat kecil dan menengah baik untuk konsumsi maupun produksi serta juga menyimpan hasil usaha mereka. Penelitian ini bertujuan untuk mengetahui dasar-dasar teori yang terkait dengan pengembangan produk-produk lembaga keuangan mikro syariah. Hasil penelitian menunjukkan bahwa pengembangan produk-produk LKMS melalui proses perencanaan perusahaan untuk mengetahui keinginan pasar, menetapkan keputusan yang strategis dalam pembentukan produk, memperbaiki produk, bahkan membuat inovasi produk-produk baru sebagai upaya peningkatan kualitas layanan dan produk jasa LKMS. Melalui prinsip syariah pada tahapan pengembangan produknya, maka produk-produk LKMS dapat memberikan variasi yang halal dan baik untuk kemaslahatan masyarakat secara umum. Upaya yang berkaitan dengan pengembangan produk menghasilkan kinerja manajemen LKMS mengarah pada pelaksanaan kegiatan berupa peningkatan produk. Hal ini sebagai wujud meningkatkan kualitas manajerial di LKMS. Kata Kunci: Pengembangan Produk dan Lembaga Keuangan Mikro Syariah